Creating an immersive game world with evolutionary fuzzy cognitive maps - CAI, Yundong (Institutional Knowledge at Singapore Management University, 2010)
An increasing number of serious games have been developed to enhance the user experiences in education and training. In order to bridge the gap of game experiences in the virtual environment and in the real life, it is crucial to generate believable characters and contexts in real-time. However, the variables to be simulated for a large-scale serious game are numerous. These variables are involved in complex causal relationships and their values change over time. In view that world modeling has not been well addressed with conventional models, this paper uses a computational model Evolutionary Fuzzy Cognitive Map (EFCM) to model the variables of the characters and contexts with the causalities among them in serious games. As an extension of FCM, E-FCM models not only fuzzy causal relationships but also probabilistic causal relationships among the variables. It also allows asynchronous updates of the variables, so that they can evolve in a dynamic and stochastic manner. An interactive evolutionary algorithm has been proposed to determine the causal relationships in E-FCM. As a result, the players can have a more engaging and immersive experience from these games.